Effect of the Precursor Metal Salt on the Oxygen Evolution Reaction for NiFe Oxide Materials - Nicolosi, Valeria (My University, 2024)
Bimetallic nickel-iron based oxides are regarded as one of the most promising catalysts for the oxygen evolution reaction (OER). In this study, we show that the precursor metal salts can affect the OER activity of the resulting Ni/Fe oxide under the same hydrothermal synthesis conditions. Pure sulfate, pure nitrate and mixed sulfate/nitrate metal salts were used to fabricate NiFe based oxide materials and to study the importance of the precursor choice for the OER. The results show that the nature of the precursor used in the synthesis of the bimetallic nickel-iron materials can influence different multi- phase catalysts to form which effects the OER.
Keywords: Bimetallic nickel-iron based oxides; oxygen evolution reaction; hydrothermal synthesis; Bimetallic nickel-iron based oxides; oxygen evolution reaction; hydrothermal synthesis